Small Details: Using One Device to Navigate Together - Reilly, Derek; Mackay, Bonnie; Watters, Carolyn; Inkpen, Kori (SIGCHI Conference on Computer Supported Cooperative Work (CSCW 2008), 2008)
We present results from a study examining the sensitivity of group navigation strategies to changes in route presentation on a shared mobile device. Two content-equivalent interfaces are compared. An interface providing textual instructions linked to regions on a route map yields reliance on text primarily, encouraging route planning and a divide-and-conquer strategy we term 'navigator and scout'. An interface combining text instructions with map segments on individual pages yields less planning, still permits nav/scout, and sees an increase in an ad-hoc 'sync and go' strategy involving more gathering around the device. Finally, when the route map is used without text, the frequency of the nav/scout strategy drops markedly as sync and go increases.